The wzc mutation mediates virulence changes in K1-type Klebsiella pneumoniae within the same patient - Teng, Gaoqin; Qin, Qiuying; Ding, Shuo; Wu, Yanchao; Fu, Yingying; Zhang, Meng; Yang, Xiaoqiang; Jin, Ye; Xu, Zhijiang; Huang, Man (Frontiers in Microbiology, 2025)
Hypervirulent Klebsiella pneumoniae (hvKp) is a major pathogen causing community-acquired infections, particularly severe diseases such as liver abscesses. Although extensive research has been conducted on the virulence mechanisms of hvKp and the genetic properties of resistance plasmids, studies on the adaptive evolution of clinical strains within the host are still limited. This study aimed to investigate the impact of genetic mutations on phenotypic changes in high-virulence K. pneumoniae within a host environment. We isolated three strains of K. pneumoniae from the same patient, two of which had identical genetic backgrounds but exhibited distinct phenotypic traits. Comparative genomic analysis was performed to identify genetic differences. A nucleotide mutation in the wzc gene was identified as a potential factor associated with changes in the mucoid phenotype. This mutation was verified using string tests and anti-centrifugal assays. Additionally, in vivo bioassays and animal infection models were conducted to further validate the findings. The comparative genomic analysis revealed a nucleotide mutation in the wzc gene, which was associated with changes in the mucoid phenotype of the strain. This was confirmed through string tests and anti-centrifugal assays. In vivo experiments and animal infection models suggested that hvKp adapts to the host by reducing capsular polysaccharide synthesis, thereby trading off some virulence for enhanced colonization capabilities. Our findings indicate that genetic mutations in hvKp can lead to significant phenotypic changes that facilitate adaptation within the host. The observed reduction in capsular polysaccharide synthesis appears to be a trade-off between virulence and colonization ability. This study provides insights into the adaptive evolution of hvKp and highlights the importance of considering intrahost genetic changes when studying the pathogenesis of hvKp. Future research should focus on further elucidating the mechanisms underlying these adaptations and their clinical implications.